Why are higher education participation rates in Germany so low? : Institutional barriers to higher education expansion - Powell, Justin J. W. [Verfasser]; Solga, Heike [Verfasser] (My University, 2011)
"Countries around the world have witnessed educational expansion at all levels, leading to the massification of tertiary education and training. Tertiary education has become a major factor of economic competitiveness in an increasingly science-based global economy and a key response to shifts in national labour markets. Within the EU, the reform of skill formation systems has been advanced by the Lisbon strategy, with the Bologna and Copenhagen processes in higher education (HE) and vocational education and training (VET) articulating and diffusing overarching goals in European skill formation. If European benchmarks call for at least 40% of all 30- to 34-year-olds to hold a tertiary-level certificate, Germany exhibits a relatively low proportion of each cohort entering HE and attaining that qualification level (28%). We analyse this 'German exceptionalism', locating a range of factors in the educational system: the institutional logic of segregation, the structure of secondary schooling, the division or schism between the organisational fields of VET and HE, and limited permeability throughout. Regardless of isomorphic pressures that led Germany to quickly implement undergraduate bachelor's (BA) and graduate master's (MA) courses of study, these factors limit the extent of HE expansion visible among other European countries." (Autorenreferat, BIBB-Doku)
Keywords: G 2.5.3 Anschlussfähigkeit von Bildungsgängen; Durchlässigkeit im Bildungssystem; Berufsbildung; Hochschulbildung; Bildungsexpansion; Europäische Integration; Europäischer Bildungsraum; Studienberechtigung; Studienplatznachfrage; Einflussfaktor; Soziale Herkunft; Soziale Umwelt